Theoretical Perspectives on Critical Thinking Teaching: Reflections from Field Experiences from a Norwegian Lower Secondary School in Comparison to Tanzanian Secondary School Teaching Practices - Leatitia Gabriel Mashaza (Journal of Education and Learning (EduLearn), 2017)
This paper presents the theoretical perspectives relevant to critical thinking as my topic of research during my teaching practice period which was conducted from 12th -28th October 2015 at Eidsvag secondary school in Bergen, Norway. As a requirement for Masters’ degree in social science education, all master students were required to engage in teaching practice in different Norwegian primary and secondary schools. Importantly, every student teacher was given a topic of concentration as a mini-research for the whole teaching practice period. My topic of research focused at exploring and gaining the theoretical and practical perspectives on critical thinking teaching by drawing some experiences from a Norwegian lower secondary school (Eidsvag skole) in reflection to secondary school teaching practice experiences in Tanzania. Therefore, in this paper, my reflections with regard to the conditions favoring the possibility for critical thinking teaching and how it was enhanced by teachers at my practice school will be discussed. Further to that, I will also present the observed challenges of which, in my view, in way or another intervened the possibility for effective critical thinking teaching to take place.